Peripheral oxytocin is associated with reduced symptom severity in schizophrenia - Rubin, Leah H. (2010)
BACKGROUND: Emerging evidence from clinical trials suggests that oral estrogen and intranasal oxytocin might reduce symptom severity in schizophrenia. Whether increases in endogenous hormones are similarly associated with improved symptoms is unknown. We investigated the effects of menstrual cycle phase and related fluctuations in peripheral hormone levels on clinical symptoms in women with chronic schizophrenia. METHOD: Twenty-three women with schizophrenia were administered the Positive and Negative Syndrome Scale (PANSS), a measure of clinical symptom severity, at two menstrual cycle phases: 1) early follicular (Days 2–4; low estrogen/progesterone) and 2) midluteal (Days 20–22; high estrogen/progesterone). Twenty-seven males with schizophrenia and 58 controls (31 female) completed testing at comparable intervals. Men were included to examine whether the relationships between clinical symptoms and hormone levels in women generalize to men. Plasma hormone assays of estrogen, oxytocin, progesterone, and testosterone were obtained. RESULTS: Female patients showed less severe symptoms during the midluteal versus early follicular phase (p’s<0.01). Oxytocin did not fluctuate across phases, but in female patients (p’s<0.01) higher oxytocin levels were associated with less severe positive symptoms and overall psychopathology. In both sexes, higher oxytocin levels were associated with more prosocial behaviors (p<0.05). CONCLUSION: Consistent with previous findings in acutely ill patients, our results suggest that clinical symptoms vary across the menstrual cycle in patients with chronic schizophrenia. Similar to recent findings regarding benefits of intranasal oxytocin, these new findings indicate that high levels of endogenous oxytocin might improve positive symptom severity and general psychopathology in women and social behaviors in both sexes.